Representasi Makna Perpisahan pada Lirik Lagu “Give Me Five” Karya JKT48: Analisis Semiotika Ferdinand de Saussure - Gunadi, Dauhah Fitriyani (Indonesian Journal Publisher, 2023)
This article contains the representation of the meaning of separation in the lyrics of the song